The Influence of Emotional and Spiritual Intelligence on The Ability to Memorise Al-Qur'an Of Junior High School Students - Zulfa Safiinatunnajah; Akif Khilmiyah (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aimed to assess the impact of emotional intelligence and spiritual intelligence on Qur'anic memorization among junior secondary school students. The approach used was quantitative with a survey method. The research subjects consisted of 103 students participating in the tahfidz program, each of whom had memorized at least one juz. The instrument used was a Likert-scale questionnaire to measure emotional intelligence, spiritual intelligence, and memory ability. Data analysis was conducted with multiple linear regression. The results of the F test show that emotional and spiritual intelligence together have a significant effect on the ability to remember the Qur'an. The partial t-test also showed that both variables had a significant effect with a p-value < 0.05. This finding confirms that emotional aspects such as self-control and motivation, as well as spiritual aspects such as closeness to God and meaning of life, contribute to students' success in memorizing the Qur'an. The coefficient of determination of 50.2% indicates that the two variables together explain more than half of the variation in memorization ability. Therefore, it is important to improve spiritual and emotional intelligence in a balanced manner to support optimal memorization results, as well as emphasize the importance of a holistic approach in teaching tahfidz.